From microbes to medicine: harnessing the gut microbiota to combat prostate cancer - Anjali Yadav; Meenakshi Kaushik; Prabhakar Tiwari; Rima Dada (Microbial Cell)
The gut microbiome (GM) has been identified as a crucial factor in the development and progression of various diseases, including cancer. In the case of prostate cancer, commensal bacteria and other microbes are found to be associated with its development. Recent studies have demonstrated that the human GM, including Bacteroides, Streptococcus, Bacteroides massiliensis, Faecalibacterium prausnitzii, Eubacterium rectale, and Mycoplasma genitalium, are involved in prostate cancer development through both direct and indirect interactions. However, the pathogenic mechanisms of these interactions are yet to be fully understood. Moreover, the microbiota influences systemic hormone levels and contributes to prostate cancer pathogenesis. Currently, it has been shown that supplementation of prebiotics or probiotics can modify the composition of GM and prevent the onset of prostate cancer. The microbiota can also affect drug metabolism and toxicity, which may improve the response to cancer treatment. The composition of the microbiome is crucial for therapeutic efficacy and a potential target for modulating treatment response. However, their clinical application is still limited. Additionally, GM-based cancer therapies face limitations due to the complexity and diversity of microbial composition, and the lack of standardized protocols for manipulating gut microbiota, such as optimal probiotic selection, treatment duration, and administration timing, hindering widespread use. Therefore, this review provides a comprehensive exploration of the GM's involvement in prostate cancer pathogenesis. We delve into the underlying mechanisms and discuss their potential implications for both therapeutic and diagnostic approaches in managing prostate cancer. Through this analysis, we offer valuable insights into the pivotal role of the microbiome in prostate cancer and its promising application in future clinical settings.